Perception of Anthropomorphism, Intelligence and Adoption of AI: A case in mobile banking - Apoorva (Gyan Management Journal, 2023)
Purpose – Artificial intelligence (AI) has completely transformed the mobile banking industry, but little is known about how particular AI features influence consumer acceptance strategies and avoidance behaviours in the literature. To address this gap, the present study examines how users’ intentions to embrace AI-based mobile banking are influenced by the pivotal characteristics of AI, perceived intelligence and anthropomorphism. Design/methodology – A cross-sectional descriptive research design was used for this study. Further, a judgemental non-probability sam pling was employed to identify the 100 respondents. The data was sub sequently analysed using PLS-Structural Equation Modeling. Findings – The results exhibit that both PI and PA positively and sig nificantly impacted consumers’ intention to adopt of AI-based mobile banking apps. It also offers theoretical underpinnings for the adoption of AI-based mobile banking apps. Furthermore, findings furnish prac tical guidance that can be instrumental for banks contemplating the implementation of AI to enhance user retention strategies. Originality/value –This study adds valuable contribution to the field by shedding light on the nuanced aspects of AI and their substantial impact on users’ intention to adopt mobile banking app services.